Observation of circularly polarized radiation from multimode undulator at HiSOR - Rybalchenko, G.V.; Morita, M.; Shirasawa, K.; Smolyakov, N.V.; Goto, K.; Hiraya, A. (Вопросы атомной науки и техники, 2001)
The linear / helical multimode undulator that is able to produce polarized radiation of any ellipticity operates successfully in Hiroshima Synchrotron Radiation Center. Polarization measurements have been performed for helical mode of undulator using IR-UV polarimeter at the beamline BL9 of the 700 MeV storage ring (HiSOR). High degree of circular polarization has been obtained. The comparison between achieved performance and numerical simulation was made. The main reason of slight distinction between them was found to be in the influence of non-undulator radiation.